Pre-weld friction stir processing mitigates hot cracking and strengthens AA6061 fusion welds - Ali Jalili; Ali Ghasemi; Mehran Torabi Kafshgari; Swee Leong Sing; Majid Pouranvari (Scientific Reports)
Abstract Hot cracking remains a significant challenge in the fusion welding of high-strength aluminum alloys, particularly AA6061, which is highly susceptible to solidification cracking in the fusion zone (FZ). This study investigates the efficacy of friction stir processing (FSP) as a pre-weld treatment to enhance the weldability of AA6061 by engineering the base metal microstructure. We demonstrate that FSP transforms AA6061 from a material highly prone to solidification cracking into one with remarkable crack resistance during fusion welding. By applying multi-pass FSP to AA6061-T6, we achieved a base metal with ultra-fine grains, which facilitated the epitaxial growth of fine grains during subsequent fusion welding. The refined grain structure in the FZ, combined with reduced dendrite arm spacing, significantly mitigated solidification cracking by improving grain coalescence and strain accommodation during solidification. Post-weld T6 heat treatment resulted in a joint efficiency of 0.95 in tensile strength, outperforming conventional fusion welding and friction stir welding. This work highlights the potential of FSP as a pre-weld treatment to convert crack-prone aluminum alloys into viable candidates for high-integrity, lightweight structural applications.